Genome Mining of the Marine Actinomycete Streptomyces sp. DUT11 and Discovery of Tunicamycins as Anti-complement Agents - Xu, Xiao-Na; Chen, Liang-Yu; Chen, Chao; Tang, Ya-Jie; Bai, Feng-Wu; Su, Chun; Zhao, Xin-Qing (Frontiers in Microbiology, 2018)
Marine actinobacteria are potential producers of various secondary metabolites with diverse bioactivities. Among various bioactive compounds, anti-complement agents have received great interest for drug discovery to treat numerous diseases caused by inappropriate activation of the human complement system. However, marine streptomycetes producing anti-complement agents are still poorly explored. In this study, a marine-derived strain Streptomyces sp. DUT11 showing superior anti-complement activity was focused, and its genome sequence was analyzed. Gene clusters showing high similarities to that of tunicamycin and nonactin were identified, and their corresponding metabolites were also detected. Subsequently, tunicamycin I, V and VII were isolated from Streptomyces sp. DUT11. Anti-complement assay showed that tunicamycin I, V, VII inhibited complement activation through the classic pathway, whereas no anti-complement activity of nonactin was detected. This is the first time that tunicamycins are reported to have such activity. In addition, genome analysis indicates that Streptomyces sp. DUT11 has the potential to produce novel lassopeptides and lantibiotics. These results suggest that marine Streptomyces are rich sources of anti-complement agents for drug discovery.